Hypochlorite bleaching of oil palm empty fruit bunches soda-aq pulp for blending with recycled newspaper / Rushdan, I. - I., Rushdan (2006)
Application of oil palm empty fruit bunch as raw materials for pulp and paper is extremely promising because of its availability and the future demand of paper in Malaysia is expected to be enormous. In this work, the effect of hypochlorite bleaching of EFB soda-anthraquinone pulp was studied. The oil palm empty fruit bunch was pulped by soda-anthraquinone pulping process and bleached by two stages of hypochlorite and alkali extraction. The pulp was treated with different bleaching temperatures, bleaching retention time and hypochlorite concentration of EFB dry weight. After bleaching, the brightness of pulps is in the range of 60 to 76% Hypochlorite concentration has the highest impact on pulp brightness compared to bleaching temperature and retention time. The pulp brightness can be predicted by varying the temperature, retention time and hypochlorite concentration.